RAYMOND CARVER: LANGUAGE AND SILENCE CARVING THE HOPELESS AMERICANS - Oliveira, Carlos Böes (Revista Prâksis, 2017)
ABSTRACT Raymond Carver was a great North American short writer in the 1970’s and 1980’s. His writings have singular characteristics, such as: a minimalist style; desperate characters in constant financial a familiar struggle; the characters’ inability to articulate any kind of concealing communication; and the presence of silence as a place of resistance. This study intends to analyze the use of language and the lack of it in the literature of Raymond Carver. The main goal of this paper is to verify how the recurrent use of silence helps as a mechanism of social resistance, and how this artifice is fundamental in maintaining the world the character inhabit from falling apart. Another aspect analyzed in this paper is how the lack of communication from the masculine characters affect their own masculinities, making them fragile. To support this study the discourse analysis from Michel Pecheux, and its theoretical presuppositions about ideology, language and the subject are applied. To analyze the use of silence in the literature of Raymond Carver, Eni Orlandi is brought to usage, as much as scholars that study Carver and theoreticians that discuss lacanian psychanalysis. It is expected to conclude that the use of silence, as a means of communication, by the author’s characters is a vulnerable strategy that this people find to avoid their social sphere from collapsing. Keywords: Raymond Carver. Discursive formation. Silence. RESUMO Raymond Carver foi um grande contista norte-americano nas décadas de 1970 e 1980. Seus escritos têm características muito marcantes, entre elas: um estilo minimalista; personagens desesperados e em constante dificuldade financeira e familiar; a incapacidade de suas personagens articularem uma comunicação conciliadora; e a presença do silêncio como local de resistência. Este estudo pretende analisar o uso da linguagem e da falta desta na literatura de Raymond Carver. O desígnio central deste trabalho é verificar como o uso recorrente do silêncio serve de mecanismo de resistência social, e como este subterfúgio utilizado pelas personagens é fundamental para evitar que o universo social dos sujeitos desmorone. Outro aspecto analisado neste artigo é como a falta de comunicação por parte das personagens masculinas afeta suas próprias masculinidades, deixando-as frágeis. Para embasar este estudo, a análise do discurso da escola de Michel Pecheux, e seus pressupostos teóricos sobre ideologia, língua e sujeito são trazidos à tona. Para analisar o uso do silêncio na literatura de Carver, Eni Orlandi é utilizada, bem como estudiosos da literatura de Raymond Carver e acadêmicos da psicanálise lacaniana. Espera-se concluir que o uso do silêncio, como forma de comunicação, pelas personagens do autor seja uma estratégia vulnerável que estes sujeitos encontram de manter o seu universo em pé. Palavras-chave: Raymond Carver. Formação discursiva. Silêncio.